PERANCANGAN SISTEM INFORMASI PENGONTROLAN DAN PENCATATAN HAFALAN AL-QUR’AN DAN IQRO MENGGUNAKAN METODE PROTOTYPE - Muhammad Adnan Priambodo; Dimas Suryo Wicaksono; Fajar Masya (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
In this final project, we aim to create a Design of Information System Control and Memorization Recording of the Qur'an and Iqro Using Prototype Methods. This website-based application is an application for controlling and recording the memorization of the Qur'an and Iqro that can be accessed with any web browser. This application is expected to be able to help teachers of the Koran during this pandemic who teach through their respective homes. Teachers can input grades and notes for students who are reading Al-Qur’an, making it easier for teachers to assess students. With the Design of Information System Control and Memorization Recording of the Qur'an and Iqro Using Prototype Methods, it is hoped that it will facilitate the work of the Koran teachers and other teachers. Can also be used for schools in need. This web application is made with an easy user interface so that beginners can easily master the application. The type of research used is descriptive qualitative research method while the data collection method used is using the method of collecting data questionnaires, literature studies and observation. The design method used is Prototype and the testing technique uses blackbox. The results of this study are a website application for memorizing the Qur'an and Iqro information systems. The conclusion of this study is that it makes it easier to manage the memorization and murojaah data of the Qur'an for online musyrif and santri.